(Bahasa) Iklan: Memahami dan Memanfaatkannya sebagai Materi Pelajaran Bahasa - Ignatius Harjanto (Widya Mandala Surabaya Catholic University, 2010)
In modern life, people cannot avoid persuasion from advertisements. Advertisers employ techniques to make claims for their products. The advertisers promise and claim in such a way that consumers may buy the products even when they do not really need them. People may disagree with and question the promises and claims of advertisements. The fact is that more consumers including students believe promises and claims in the advertisements than those who question them. Consumers who question the promises and claims of advertisements argue that advertising is childish, dumb, and a bunch of lies. This article discusses the language of advertising and how advertisers persuade and argue. To clarify the discusion, examples of claims used in the advertisements are given. The paper is ended with discussion of using advertisements for language teaching materials